Construction of the “Full Path” of restorative effects on older adults’ mental health in parks under seasonal differences: taking Changchun as an example - Yan, Tianjiao; Leng, Hong; Yuan, Ziqing (Frontiers in Public Health, 2024)
With the aging and older adults’ mental health problems in China, more attention has been paid to the restorative environment. As an important restorative environment in the city, the mental health restorative effect of park environment has been confirmed. However, further exploration is needed to determine whether winter parks have positive effects, their differences from non-winter parks, and the specific pathways of these effects. Therefore, this study constructed a “full path” for the restorative effects of older adults’ mental health in parks under seasonal differences, including four components: perceived environment, affective feedback, behavioral feedback, and restorative effect, forming four pathways. Based on this, this study obtained 211 and 240 sample data in winter and non-winter parks, and verified the validity of various hypotheses and mediation paths using structural equation models. It found that: 1) overall restorative effects existed in different seasons; 2) in winter, perceived environmental assessment was not a direct antecedent of restorative effects, and affective feedback and MVPA (Moderate and Vigorous Physical Activity) feedback were important mediating factors, and the chain mediated pathway existed; 3) in non-winter, both direct , indirect and chain mediated effects existed, and affective feedback and LPA (Low Physical Activity) feedback were important mediating factors. Based on this, this study divided parks into “affective inducing” and “behavioral promoting” types, and proposed corresponding planning priorities to positively intervene in planning and design practices.